Friends or strangers? Strategic uncertainty and coordination across experimental games of strategic complements and substitutes - Gabriele Chierchia; Fabio Tufano; Giorgio Coricelli (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
It is commonly assumed that friendship should generally benefit agents' ability to tacitly coordinate with others. However, this has never been tested on two "opposite poles" of coordination, namely, games of strategic complements and substitutes. We present an experimental study in which participants interact with either a friend or a stranger in two classic games: the stag hunt game, which exhibits strategic complementarity, and the entry game, which exhibits strategic substitutability. Both games capture a frequent trade-off between a potentially high paying but uncertain action and a lower paying but safe alternative. We find that, relative to strangers, friends exhibit a propensity towards uncertainty in the stag hunt game, but an aversion to uncertainty in the entry game. Friends also "tremble" less than strangers, coordinate better and earn more in the stag hunt game but these advantages are largely decreased, and almost entirely lost in the entry game. Friendship thus appears to have a very different impact on coordination games involving strategic complements and substitutes. We further investigate the role of interpersonal similarities and friendship qualities in this differential impact.
Keywords: C72; C92; D80; 330; coordination; entry game; friendship; strategic complementarity; strategic substitutability; stag hunt game; strategic uncertainty